The first forests - Attenborough, Richard, 1926-; British Broadcasting Corporation (Wilmette : Films Inc, 1981)
Naturalist Richard Attenborough traces the movement and adaptation of algae and moss-like palnts from a water environment to the land. Also uses microphotography to reveal unsuspected details in moses, liverworts, ferns, cycads, and conifers
Keywords: Plants -- Evolution; Botany -- Anatomy; Adptation (Biology)